When Things Fall Apart It Results in Disgrace: Protagonist Analysis of David Lurie in Disgrace by J.M. Coetzee and Okonkwo in Things Fall Apart by Chinua Achebe: Exploring the Effects of Colonization on Protagonists (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper will deal with two novels, namely Disgrace by J.M. Coetzee and Things Fall Apart by Chinua Achebe. Disgrace is set in South Africa and Things Fall Apart in Nigeria. The British Empire colonized a few countries all through Africa amid the nineteenth century. It turned into a regularly utilized name for the pioneer control. The task of imperialism was conveying riches toward the western countries through the misuse of different countries. The British Empire colonized the countries thusly as well as the general population living inside the countries. One could state that they colonized both the countries and its brains. They fundamentally considered them to be kids who should have been ruled for their madness and by removing their way of life, religion and public activity they appeared to trust that they could control and lead the colonized individuals. Another part of colonization is the injury that the colonized individuals endured in the change of turning into a frontier subject. Ania Loomba says in his book ColonialismPost Colonialism (1998),The most across the board understanding was that 'deculturation' was the reason for rising craziness. The breakdown of customary structures and the strains of 'present day' society had actually unhinged Africans who were unfit to adapt to change. (119)